PERILAKU MENCUCI TANGAN PENGUNJUNG RUMAH SAKIT DI RUMAH SAKIT SWASTA YOGYAKARTA - Maria Theresia, Siwi Ikaristi (Universitas Jenderal Achmad Yani Yogyakarta, 2017)
Background: Visitors take part in the occurrence of nosocomial infections. Their hands are a reservoir for microorganisms that can be transmitted to patients as individuals susceptible for secondary infections. Hand washing before and after visiting patients is the easiest way to remove colonies of microorganisms in the hands. The alcohol-based hand rub is available for visitors in the hospital’s rooms but there are no evaluation by hospital managemen. Objective: This study aims to evaluate hand-washing behavior of visitors at a private hospital in Yogyakarta. Methods: Research method used descriptive quantitative survey. Sample was taken by accidental sampling from 2015 - 2017 and got 229 respondents. Data collection by observation in the room includes ICU, ICCU, surgical ward and post partum ward. Results: The result showed that percentage visitors who did not wash their hands before and after entering in the ICU was 50% and 83.33%, in the medical ward was 80% and 81.82%, in the ICCU was 81,73% and 70,19% and in the post partum ward was 57,5% and 30%. Conclusion: The high percentage of respondents who did not wash their hands before and after visiting patients is an important concern because they will carry microorganisms that can be transmitted to others. Suggestions for hospital are to campaign, make banners and leaflets for health promotion of the importance washing hands before and after visiting patients in the hospital for public. Key words: Hand washing, visitors, nosocomial infection.